The Influence Of Neighbourhood Spatial Configuration On Residents’ Physical Activity And Health Based On The Cpted Approach: A Case Study Of Penang, Malaysia - Safizadeh, Mina (2023)
Residents’ physical activity and health are considered among the crucial urban planning concerns. The relationship between spatial configuration of the built environment and human movement patterns is widely supported in the literature. Despite the growing research on the relationship between the built environment and health, there is still a gap in the theoretical aspects, especially in Malaysian context. In this sense, this study combined the two significant and influencing concepts of Space Syntax and Crime Prevention through Environmental Design (CPTED) to empirically investigate their impact on public physical activity and health. Moreover, this study examined the mediating role of perception of safety and fear of crime in this relationship. The present study employed a quantitative research approach. In this study, for the first time, an axial map of the entire Penang Island street network was drawn, and the most comprehensive space syntax analyses (i.e., calculations of integration, connectivity, and control value) were performed using the DepthMapX software. The study further employed a survey method for the next stage of data collection, including an on-site observation checklist to evaluate CPTED principles on a street scale and a self-administered questionnaire containing several sections about the respondents’ physical activity, general health, perception of safety, fear of crime, and their houses’ elements of CPTED. A stratified systematic sampling method was used to select samples among stratum (i.e., global integration). A total number of 211 participants from the selected neighbourhood were involved in this study.